Substantial planar plastic anisotropy in inorganic Mg 3 Bi 2 single crystals - Tianyu Zhang; Jin Yan; Jin Ke; Peng Zhao; Yuexin Zhou; Yifan Zhou; Sheng Ye; Yao Xu; Baopeng Ma; Shanghao Chen; Jinxuan Cheng; Jiahui Chen; et al. (Proceedings of the National Academy of Sciences, 2025)
Elucidating the fundamental microscopic mechanisms governing plastic deformation is crucial for the rational design of functional materials with tailored mechanical properties. Recent advances in Mg 3 Bi 2 -based thermoelectric materials have revealed exceptional room-temperature ductility in these compounds. However, the origin of their plastic behavior remains elusive. Herein, we report a pronounced in-plane plastic anisotropy in single-crystalline Mg 3 Bi 2 . Micropillar compression reveals that the observed anisotropy is critically dependent on the activation of single versus double slip systems, and superior plastic deformability can be achieved once the double slip system is activated. The interatomic potential for Mg 3 Bi 2 was developed via the machine learning approach, and molecular dynamics simulations establish that the crystallographic orientation-dependent activation of competing slip systems constitutes the fundamental origin of the plastic anisotropy in Mg 3 Bi 2 . Additionally, our study demonstrates that pyramidal a dislocations play a crucial role in the plasticity of Mg 3 Bi 2 .